Anxiety and insomnia prevalence during the COVID-19 pandemic among healthcare workers in the Ministry of Health and Prevention- United Arab Emirates - Alrand, Hussain; Harbi, Alya; Razzak, Hira Abdul; Eltabbakh, Mohamed Tawfik; Al Shaali, Lubna; E. Salama, Rasha (International Journal Of Community Medicine And Public Health, 2022)
Background: COVID-19 pandemic and lockdown have the potential to influence the mental health of the frontline healthcare workers (HCWs), working in the time of crisis. Hence, it is essential to monitor the anxiety, sleep, along with the other mental health concerns to realize the interceding risk factors as well as to inform tailored interventions. This study therefore aims to detect the psychological impact of COVID-19 experienced by the healthcare professionals during the COVID-19 pandemic working in the Ministry of Health and Prevention (MOHAP) facilities. Methods: A descriptive cross-sectional study was carried out between 25 October 2020 to 30 September 2021 by recruiting 404 healthcare providers currently working in different hospitals of the MOHAP. Results: Of 404 healthcare workers, 76.7% were females and 23.3% were males. About 35.6% were aged 36-45 years. The majority of the participants were non-locals (84.4), 23.5% were doctors/physicians, and 58.7% were nurses, 7.7% were pharmacist, remaining were other healthcare providers. Overall, 10.6% and 3.2% of all healthcare workers reported severe symptoms of anxiety, and insomnia respectively. Only age, gender, qualification, worried about being infected with COVID-19 and likelihood of being infected from COVID-19 showed statistically significant results (p<0.05). Conclusions: The pandemic with respect to the COVID-19 tends to have a noteworthy impact on the mental health of healthcare workers. This evidence indicates that substantial proportion of healthcare workers may experience sleep disturbances and anxiety during the outbreak suggesting a necessity to indicating traditions of mitigating the risks of mental health and regulate interventions under pandemic situations.